Tourism Challenges amid COVID-19 - Pantić, Nemanja (Hotel and Tourism Management, 2021)
Conclusions of the 6th Tourism International Scientific Conference (TISC) held at the Faculty of Hotel Management and Tourism in Vrnja?ka Banja, June 3rd –June 5th, 2021